Pengembangan Modul Ajar Mata Pelajaran Bahasa Indonesia Di Kelas VIII SMP Swasta Idanoi - Gea, Theresia Jeni Kristina; Bawamenewi, Arozatulo; Ndruru, Mastawati; Waruwu, Lestari (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop a teaching module for Indonesian language subjects on poetry analysis for eighth-grade students at Idanoi Private Junior High School. This study uses qualitative methods. Data was obtained through observation, interviews, and documentation, and using the Borg and Gall model, namely (Introduction (Research and Information Collecting), Planning Research (Planning), Design Development (Develop Preliminary of Product), Preliminary Field Testing, Revision of Limited Field Test Results (Main Product Revision), Main Field Test, Revision of Wider Field Test Results (Operational Product Revision), Feasibility Testing (Operational Field Testing), Final Revision of Feasibility Test Results (Final Product Revision), Dissemination and Implementation of the Final Product (Dissemination and Implementation). The subjects of this study were eighth-grade students of Idanoi Private Junior High School. The results showed that the poetry analysis teaching module developed was declared to have very good feasibility based on validation from three experts: material experts reaching (76.2%), language experts reaching (74%), and design experts reaching (85.7%). The practicality of the developed media was assessed through student response questionnaires in small group trials reaching (87%), which indicates that this media is very practical to use in learning. The effectiveness of the developed media was measured by the results of student learning tests, which showed a percentage of completeness reaching 70% with an average score of 90, which meets the Learning Objective Achievement Criteria. it can be concluded that the Teaching Module is feasible, practical, and effective for use in learning Poetry material at Idanoi Private Junior High School.